INTEGRATION PROCESSES IN CENTRAL ASIA. PROSPECTS FOR A COMMON MARKET - RAKHMATULLINA, Gulnur (CENTRAL ASIA AND THE CAUCASUS, 2005)
Globalization processes have a growing effect on the development of individual countries and the world economy, with the Central Asian states, among others, being drawn into their orbit.The advantages of globalization are realized precisely at the integration and regional levels. That is why it is so important today to implement the initiative launched by President Islam Karimov of Uzbekistan for creating a Central Asian Common Market (CACM). The idea is that this market should include Kazakhstan, Kyrgyzstan, Tajikistan and Uzbekistan. However, an analysis of the development of their cooperation shows that integration processes in the region have not yet reached the desired intensity and that many problems of interaction between these states in the real sector of the economy and in the social and cultural spheres have not been resolved.A key problem of economic cooperation between the Central Asian (CA) states is rational use of their water and energy resources. With this aim in view, annual agreements are concluded on guaranteed supply of coal, fuel oil and gas from Kazakhstan and Uzbekistan to Kyrgyzstan, while the latter undertakes to supply the agriculture of these states with water during the vegetation period. But since Uzbekistan and Kazakhstan fail to perform their obligations in full, Kyrgyzstan’s thermal power stations cannot reach the desired parameters, which puts additional pressure on the Naryn hydropower system, leading to an increase in water release from the Toktogul Reservoir and to a reduction in its volume. In other words, the mechanism for mutual supply of water and energy resources is virtually inoperative. If such practices continue, the level of the Toktogul Reservoir will drop to a critical point known as “dead storage.”In addition, there are still contradictions between Astana and Tashkent over Uzbekistan’s intake of water from Syr Darya in the vegetation period beyond the agreed limit and the problem of pollution of this river. The supply of water to Kazakhstan’s southern regions remains one of the most important problems for our republic, which could lead to tensions in interstate relations.In order to improve the mechanism for rational use of water and energy resources, a project for the establishment of an International Water and Energy Consortium was put on the agenda back in the days of the Central Asian Economic Community (CAEC). Unfortunately, this project is still at the discussion stage